Parallel electron heating in the magnetospheric inflow region. Issue 10 (21st May 2017) - Wang, Shan; Chen, Li‐Jen; Hesse, Michael; Wilson, Lynn B.; Bessho, Naoki; Gershman, Daniel J.; Ergun, Robert E.; Phan, Tai D.; Burch, James L.; Dorelli, John C.; Giles, Barbara; Torbert, Roy B.; et al.
Abstract: We analyzed 20 reconnection events observed by the Magnetosphere MultiScale mission, finding that in a subregion of the magnetospheric inflow, the electron temperature parallel to the magnetic field ( T e || ) decreases toward the separatrix with increasing densities. Such T e || variation is not consistent with the heating through the parallel potential mechanism for magnetospheric electrons. Associated with the change in T e||, low‐energy gyrotropic magnetosheath‐like electrons are observed. These electrons may come from the magnetosheath, penetrate to the magnetospheric side possibly due to waves in the lower hybrid frequency range, and do not experience as much energization as those from deeper in the magnetosphere. In addition, as T e || decreases, the high‐energy field‐aligned phase‐space densities decrease or fluctuate significantly over time. Wave‐particle interaction might produce energy conversion and cause the high‐energy phase‐space density variations. Key Points: A sublayer in the magnetospheric inflow with decreasing T e || and increasing density toward the separatrix is shown to be a common feature Penetration of fresh magnetosheath electrons may partially account for the T e || decrease and density increase toward the separatrix High‐energy electron phase‐space density variations in magnetosphere inflow are collocated with waves in the lower hybrid frequency range